Environmental Conditions Outweigh Geographical Contiguity in Determining the Similarity of nifH-Harboring Microbial Communities in Sediments of Two Disconnected Marginal Seas - Zhou, Haixia; Dang, Hongyue; Klotz, Martin G. (Frontiers in Microbiology, 2016)
Ecological evidence suggests that heterotrophic diazotrophs fueled by organic carbon respiration in sediments play an important role in marine nitrogen fixation. However, fundamental knowledge about the identities, abundance, diversity, biogeography and controlling environmental factors of nitrogen-fixing communities in open ocean sediments is still elusive. Surprisingly, little is known also about nitrogen-fixing communities in sediments of the more research-accessible marginal seas. Here we report on an investigation of the environmental geochemistry and putative diazotrophic microbiota in the sediments of Bohai Sea, an eutrophic marginal sea of the western Pacific Ocean. Diverse and abundant nifH gene sequences were identified and sulfate-reducing bacteria were found to be the dominant putative nitrogen-fixing microbes. Community statistical analyses suggested bottom water temperature, bottom water chlorophyll a content (or the covarying turbidity) and sediment porewater Eh (or the covarying pH) as the most significant environmental factors controlling the structure and spatial distribution of the putative diazotrophic communities, while sediment Hg content, sulfide content and porewater SiO32--Si content were identified as the key environmental factors correlated positively with the nifH gene abundance in Bohai Sea sediments. Comparative analyses between the Bohai Sea and the northern South China Sea identified a significant composition difference of the putative diazotrophic communities in sediments between the shallow-water (estuarine and nearshore) and deep-water (offshore and deep-sea) environments, and sediment porewater dissolved oxygen content, water depth and in situ temperature as the key environmental factors tentatively controlling the species composition, community structure and spatial distribution of the marginal sea sediment nifH-harboring microbiota. This confirms the ecophysiological specialization and niche differentiation between the shallow-water and deep-water sediment diazotrophic communities and suggests that the in situ physical and geochemical conditions play a more important role than geographical contiguity in determining the community similarity of the diazotrophic microbiota in marginal sea sediments.